2011
DOI: 10.1007/bf03326255
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of hydrolytic enzymes in haloarchaeal strains isolated from salt lake

Abstract: ABSTRACT:Production of ten hydrolytic enzymes was qualitatively studied on the haloarchaeal strains isolated from Aran-Bidgol hypersaline lake in the central desert area of Iran. A total of 293 haloarchea strains were selected among 300 extremely halophilic isolated prokaryotes. Accordingly, 142, 141, 128, 64, 38, 16, 7, 3 and 1 archaeal isolates were able to produce DNase, amylase, lipase, inulinase, pullulanase, protease, cellulase, chitinase and xylanase, respectively. None was able to produce pectinase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 38 publications
(36 reference statements)
2
18
0
Order By: Relevance
“…The most enzyme producers belonged to Halorubrum. The phylogenetic analysis revealed that Halorubrum and Haloarcula are two dominant halo archaeal genera that showed high rate enzyme production [31]. Eleviet al (2004) studied the production of amylase, protease and lipase in halo archaea.…”
Section: Volume 56mentioning
confidence: 99%
“…The most enzyme producers belonged to Halorubrum. The phylogenetic analysis revealed that Halorubrum and Haloarcula are two dominant halo archaeal genera that showed high rate enzyme production [31]. Eleviet al (2004) studied the production of amylase, protease and lipase in halo archaea.…”
Section: Volume 56mentioning
confidence: 99%
“…Such demand has generated the search for new enzymes able to support the aggressive conditions of some industrial processes. Today, most enzymes do not show the same performance when they are exposed to extreme conditions such as high temperatures, acid or alkaline pH levels, denaturing, etc 3, 4. This situation has led to extremophile micro‐organism research to understand the metabolic adaptation of these micro‐organisms necessary for them to survive extreme conditions; these modifications are based on diverse enzymatic changes 5…”
Section: Introductionmentioning
confidence: 99%
“…The production of other hydrolytic enzymes was studied qualitatively in haloarchaeal strains isolated from the AranBidgol hypersaline lake in the central desert area of Iran [265] and the Tuzkoy salt mine in Central Anatolia, Turkey. Inulinase production by Halorubrum, Haloarcula and Natrinema, DNase production by Halorubrum and Haloarcula, and gelatinase production by Haloarcula and Natrinema have been reported from the Tuzkoy salt mine and Aran-Bidgol hypersaline lake [266].…”
Section: Other Hydrolytic Enzymesmentioning
confidence: 99%